toner
The toner formulation, which includes amorphous polyester, hydrocarbon wax, and a copper phthalocyanine derivative with specific functional groups, addresses the challenges of color gamut expansion and stability in cyan toners by enhancing dispersibility and charging stability.
Patent Information
- Application Number
- JP2021064685
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-06
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2041-04-06
AI Technical Summary
Existing cyan toners using copper phthalocyanine as a colorant face challenges in achieving both expanded color gamut and stable color, due to insufficient dispersibility of copper phthalocyanine crystals which affects charging properties and color stability.
A toner formulation incorporating amorphous polyester, hydrocarbon wax, and a copper phthalocyanine composition, where the copper phthalocyanine derivative contains a sulfo group, an alkyl group, or a sulfonic acid alkyl ester group, enhancing dispersibility and charging stability.
The toner achieves both expanded color gamut and improved color stability, with the sulfo group interacting with the amorphous polyester and the alkyl group interacting with the hydrocarbon wax to enhance dispersibility and charging properties.
Smart Images

Figure 0007654448000001 
Figure 0007654448000002 
Figure 0007654448000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a toner used in an electrophotographic system, an electrostatic recording system, an electrostatic printing system, and a toner jet system. [Background technology]
[0002] In recent years, full-color electrophotographic copiers have become widespread, and their application in the printing market is also progressing. High image quality is one of the performance requirements for the printing market, and stability in terms of expanding the color gamut and not changing the color tone is also important. In order to expand the color gamut, pigments as colorants are being studied, and cyan pigments are no exception. Currently, copper phthalocyanine, a type of pigment, is preferably used as a colorant for cyan toner. Copper phthalocyanine has excellent performance in terms of cost and light resistance. However, copper phthalocyanine has strong crystallinity and tends to have strong cohesive forces between copper phthalocyanine crystal particles, which tends to lead to insufficient dispersion in a medium such as an organic solvent or a molten resin, etc. Insufficient dispersion of copper phthalocyanine crystal particles tends to cause a decrease in the coloring power and chargeability of the toner. Patent Document 1 discloses a technique for improving the dispersibility of pigments in toner particles by incorporating a copper phthalocyanine derivative in the toner particles. However, although derivatives in which functional groups have been added to copper phthalocyanine can expand the color gamut by improving dispersibility, there is still room for improvement in terms of color stability related to charge retention. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2020-67527 A Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present invention is to solve the above problems and to achieve both an expansion of the color gamut and color stability. [Means for solving the problem]
[0005] The present invention provides a toner having toner particles containing an amorphous polyester, a hydrocarbon wax, and a copper phthalocyanine composition, The hydroxyl value of the amorphous polyester is 40 mgKOH / g or more and 90 mgKOH / g or less, The copper phthalocyanine composition comprises: CI Pigment Blue 15:3 and a copper phthalocyanine derivative, the copper phthalocyanine derivative being a compound represented by the following general formula (1):
[0006] [ka] [In the formula, R1 to R8 each represent a hydrogen atom, a sulfo group, an alkyl group, or a sulfonic acid alkyl ester group, At least one of R1 to R8 is a sulfo group; At least one of R1 to R8 is an alkyl group or a sulfonic acid alkyl ester group, and the alkyl group and the alkyl group contained in the sulfonic acid alkyl ester group are alkyl groups having 5 to 40 carbon atoms.] Effect of the Invention
[0007] According to the present invention, it is possible to provide a toner that achieves both an expanded color gamut and color stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The preferred toner configuration in the present invention will be described in detail below.
[0009] The toner of the present invention has toner particles containing an amorphous polyester, a hydrocarbon wax, and a copper phthalocyanine composition, the amorphous polyester having a hydroxyl value of 40 mgKOH / g or more and 90 mgKOH / g or less, the copper phthalocyanine composition containing copper phthalocyanine and a copper phthalocyanine derivative, and the copper phthalocyanine derivative is a compound represented by the following general formula (1).
[0010] [ka] [In the formula, R1 to R8 each represent a hydrogen atom, a sulfo group, an alkyl group, or a sulfonic acid alkyl ester group, At least one of R1 to R8 is a sulfo group; At least one of R1 to R8 is an alkyl group or a sulfonic acid alkyl ester group, and the alkyl group and the alkyl group contained in the sulfonic acid alkyl ester group are alkyl groups having 5 to 40 carbon atoms.]
[0011] The present inventors have found that by using a copper phthalocyanine derivative having a sulfo group and an alkyl group or a sulfonic acid alkyl ester group at the same time, it is possible to achieve both an expansion of the color gamut and color stability. Although the details of the mechanism are not clear, it is presumed as follows.
[0012] It is important that the copper phthalocyanine derivative in the present invention has a sulfo group. It is believed that the sulfo group interacts with the hydroxyl group site of the amorphous polyester, which is the binder resin, to affect the electronic state and cause a change in the light absorption. As a result of extensive research by the present inventors, it was found that a derivative having a sulfo group interacts with the amorphous polyester resin to exert a sufficient effect.
[0013] On the other hand, the presence of a sulfo group increases moisture adsorption, which causes a problem of poor charge retention. The present inventors have found that the copper phthalocyanine derivative can be provided with an alkyl group or a sulfonic acid alkyl ester group in addition to a sulfo group to simultaneously solve the problem of poor charge retention. The mechanism behind this has also not been clarified, but is presumed to be as follows.
[0014] It is important that the toner in the present invention contains a hydrocarbon wax. In general, hydrocarbon wax has no polar group, so it is less likely to leak charge and has higher charge retention than amorphous polyester. It is speculated that the charge stability is increased by the interaction between this hydrocarbon wax and the alkyl group of the copper phthalocyanine derivative, compared to when only a sulfo group is present.
[0015] The preferred configurations of the toner and derivatives in the present invention will be described in detail below.
[0016] <Toner raw materials> The binder resin for toner and the raw materials of the toner particles used in the present invention will be described below.
[0017] <Colorant (copper phthalocyanine)> The toner particles according to the present invention contain copper phthalocyanine crystals as a colorant. In terms of stability and color gamut, CI Pigment Blue 15:3 or CI Pigment Blue 15:4 is preferred.
[0018] The content of the copper phthalocyanine crystals in the toner particles is preferably 1 part by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the binder resin in the toner particles.
[0019] <Copper phthalocyanine derivatives> In the present invention, it is important to use the copper phthalocyanine derivative having the above-mentioned sulfo group and an alkyl group or a sulfonic acid alkyl ester group in order to improve the color gamut and color stability. It is believed that the interaction of the sulfo group with the hydroxyl group site of the amorphous polyester, which is the binder resin, affects the electronic state and causes a change in the absorption wavelength. At the same time, it is presumed that the presence of an alkyl group or a sulfonic acid alkyl ester group interacts with the wax, improving the electrostatic retention.
[0020] The pigment containing a copper phthalocyanine derivative into which a substituent such as a sulfo group, an alkyl group, or a sulfonic acid alkyl ester group has been introduced is not particularly limited, and can be produced, for example, by the following production method.
[0021] One method is to mix a synthetic copper phthalocyanine obtained by reacting phthalic anhydride, a urea compound, and metallic copper with a copper phthalocyanine derivative having a sulfonic acid compound or an alkyl-derived substituent, and then grind it wet or dry to form a pigment. Alternatively, a commercially available unsubstituted copper phthalocyanine pigment, such as CI Pigment Blue 15:3 or CI Pigment Blue 15:4, can be mixed wet or dry with a copper phthalocyanine derivative having a sulfo group, an alkyl group, or a sulfonic acid alkyl ester group.
[0022] Here, the mixing ratio of the unsubstituted copper phthalocyanine pigment to the copper phthalocyanine derivative having a substituent of a sulfo group, an alkyl group, or a sulfonic acid alkyl ester group is preferably 20:1 to 100:1 in terms of mass ratio.
[0023] The content of the pigment is preferably 2 parts by mass or more and 30 parts by mass or less with respect to 100 parts by mass of the binder resin.
[0024] In the copper phthalocyanine derivative having a substituent of a sulfo group, an alkyl group, or a sulfonic acid alkyl ester group, the average introduction amount of the substituent of the sulfo group, the alkyl group, or the sulfonic acid alkyl ester group is preferably 0.5 or more and 4.0 or less.
[0025] The "average amount of substituents introduced" of a sulfo group, an alkyl group, or an alkyl sulfonate group means the average number of substituents in the formula (1), and can be measured by an analytical means such as X-ray fluorescence measurement (XRF) or a time-of-flight mass spectrometer (TOF-MS).
[0026] <Amorphous polyester resin> As the binder resin used in the toner of the present invention, an amorphous polyester resin is important. By having a hydroxyl group portion, the resin interacts with the sulfo group portion of the copper phthalocyanine derivative to change the electronic state, and the light absorption is changed, thereby achieving an expansion of the color gamut.
[0027] Monomers used in the polyester unit of the polyester resin include polyhydric alcohols (divalent or trivalent or higher alcohols), polyvalent carboxylic acids (divalent or trivalent or higher carboxylic acids), their acid anhydrides or their lower alkyl esters. When preparing a branched polymer, it is effective to partially crosslink the binder resin molecule, and for this purpose, it is preferable to use a polyfunctional compound having a valence of three or more. Therefore, it is preferable to include a trivalent or higher carboxylic acid, its acid anhydride or its lower alkyl ester, and / or a trivalent or higher alcohol as the raw material monomer for the polyester unit.
[0028] As the polyhydric alcohol monomer used in the polyester unit of the polyester resin, the following polyhydric alcohol monomers can be used.
[0029] Examples of the dihydric alcohol component include ethylene glycol, propylene glycol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, diethylene glycol, triethylene glycol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 2-ethyl-1,3-hexanediol, hydrogenated bisphenol A, and bisphenol represented by formula (A) and its derivatives;
[0030] [ka] (In the formula, R is an ethylene or propylene group, x and y are each an integer of 0 or more, and the average value of x+y is 0 or more and 10 or less.)
[0031] Diols represented by formula (B);
[0032] [ka] Examples include:
[0033] Examples of trihydric or higher alcohol components include sorbitol, 1,2,3,6-hexanetetrol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerol, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, and 1,3,5-trihydroxymethylbenzene. Among these, glycerol, trimethylolpropane, and pentaerythritol are preferably used. These dihydric alcohols and trihydric or higher alcohols can be used alone or in combination.
[0034] As the polybasic carboxylic acid monomer used in the polyester unit of the polyester resin, the following polybasic carboxylic acid monomers can be used.
[0035] Examples of divalent carboxylic acid components include maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, phthalic acid, isophthalic acid, terephthalic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, malonic acid, n-dodecenylsuccinic acid, isododecenylsuccinic acid, n-dodecylsuccinic acid, isododecylsuccinic acid, n-octenylsuccinic acid, n-octylsuccinic acid, isooctylsuccinic acid, isooctylsuccinic acid, anhydrides of these acids, and lower alkyl esters thereof. Of these, maleic acid, fumaric acid, terephthalic acid, and n-dodecenylsuccinic acid are preferably used.
[0036] Examples of trivalent or higher carboxylic acids, their anhydrides or their lower alkyl esters include 1,2,4-benzenetricarboxylic acid, 2,5,7-naphthalenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, 1,2,4-butanetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, 1,3-dicarboxyl-2-methyl-2-methylenecarboxypropane, 1,2,4-cyclohexanetricarboxylic acid, tetra(methylenecarboxyl)methane, 1,2,7,8-octanetetracarboxylic acid, pyromellitic acid, empol trimer acid, their anhydrides or their lower alkyl esters. Among these, 1,2,4-benzenetricarboxylic acid, i.e., trimellitic acid or its derivatives, is particularly preferred because it is inexpensive and easy to control the reaction. These divalent carboxylic acids and trivalent or higher carboxylic acids can be used alone or in combination.
[0037] If the polyester resin is the main component, it may be a hybrid resin containing other resin components. For example, a hybrid resin of a polyester resin and a vinyl resin can be mentioned. As a method for obtaining a reaction product of a vinyl resin or a vinyl copolymer unit and a polyester resin such as a hybrid resin, a method of carrying out a polymerization reaction of one or both resins in the presence of a polymer containing a monomer component capable of reacting with each of the vinyl resin, the vinyl copolymer unit, and the polyester resin is preferred.
[0038] For example, among the monomers constituting the polyester resin component, those capable of reacting with the vinyl copolymer include unsaturated dicarboxylic acids such as phthalic acid, maleic acid, citraconic acid, itaconic acid, and their anhydrides, etc. Among the monomers constituting the vinyl copolymer component, those capable of reacting with the polyester resin component include those having a carboxyl group or a hydroxyl group, and acrylic acid or methacrylic acid esters.
[0039] In the present invention, if the binder resin is mainly composed of a polyester resin, various resin compounds conventionally known as binder resins can be used in combination with the vinyl resins described above. Examples of such resin compounds include phenol resins, natural resin-modified phenol resins, natural resin-modified maleic resins, acrylic resins, methacrylic resins, polyvinyl acetate resins, silicone resins, polyester resins, polyurethanes, polyamide resins, furan resins, epoxy resins, xylene resins, polyvinyl butyral, terpene resins, coumaroindene resins, and petroleum-based resins.
[0040] It is important that the amorphous polyester resin of the present invention has a hydroxyl value of 40 mgKOH / g or more and 90 mgKOH / g or less. When the hydroxyl value is within this range, the interaction with the sulfo group of the copper phthalocyanine derivative is strengthened, and the effect of the present invention can be achieved. If the hydroxyl value is less than 40 mgKOH / g, the interaction with the resin is weakened, and effective color gamut expansion cannot be achieved. If the hydroxyl value is more than 90 mgKOH / g, the moisture adsorption of the resin itself increases, and the target charge retention cannot be met.
[0041] The binder resin of the present invention may be a mixture of a low molecular weight binder resin L and a high molecular weight binder resin H. From the viewpoint of low temperature fixability and hot offset resistance, the content ratio (H / L) of the high molecular weight binder resin H to the low molecular weight binder resin L is preferably 10 / 90 or more and 60 / 40 or less on a mass basis.
[0042] From the viewpoint of hot offset resistance, the peak molecular weight of the high molecular weight binder resin H is preferably from 10000 to 20000. Also, from the viewpoint of charging stability in a high temperature and high humidity environment, the acid value of the high molecular weight binder resin is preferably from 2 mgKOH / g to 20 mgKOH / g.
[0043] From the viewpoint of low-temperature fixability, the number average molecular weight of the low-molecular-weight binder resin L is preferably 3000 to 7000. Moreover, from the viewpoint of charge stability in a high-temperature and high-humidity environment, the acid value of the low-molecular-weight binder resin is preferably 10 mgKOH / g or less.
[0044] <Release agent> It is important to add a hydrocarbon wax as a release agent. It is presumed that the interaction of the hydrocarbon wax with the alkyl group portion of the copper phthalocyanine derivative reduces the charge leakage path and improves the charge retention. Examples of the hydrocarbon wax include low molecular weight polyethylene, low molecular weight polypropylene, alkylene copolymer, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax. Among these waxes, Fischer-Tropsch wax is preferred from the viewpoint of the coloring power and moderate charging property of the toner.
[0045] The wax content in the toner particles is preferably 0.5 parts by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the binder resin in the toner particles. In addition, a large molecular weight is one example of a constitution that is less susceptible to charge leakage. In an endothermic curve during temperature rise measured by a differential scanning calorimeter (DSC), the peak temperature of the maximum endothermic peak present in the range of 30°C to 200°C is preferably 70°C to 130°C.
[0046] <Charge control agent> The toner particles according to the present invention may contain a charge control agent, if necessary. As the charge control agent, a metal compound of an aromatic carboxylic acid is preferable, from the viewpoints of being colorless, having a high charging speed of the toner, and being capable of stably maintaining a constant charge amount.
[0047] Examples of negative charge control agents include metal salicylate compounds, metal naphthoate compounds, metal dicarboxylate compounds, polymeric compounds having sulfonic acid or carboxylic acid on the side chain, polymeric compounds having sulfonate or sulfonate ester on the side chain, polymeric compounds having carboxylate or carboxylate ester on the side chain, boron compounds, urea compounds, silicon compounds, and calixarenes.
[0048] The charge control agent may be added internally or externally to the toner particles.
[0049] The content of the charge control agent in the toner particles is preferably 0.2 parts by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the binder resin in the toner particles.
[0050] <Metal salts> The toner of the present invention preferably contains a metal salt. It is believed that the sulfo group site of the derivative of the present invention can interact with the metal salt. It is presumed that the light absorption is easily changed by interacting not only with the resin but also with the metal salt, and the color gamut is further expanded.
[0051] The metal salt in the present invention includes metal salts such as calcium carbonate, strontium titanate, calcium sulfate, and barium sulfate. Calcium carbonate is more preferable because its refractive index is close to that of amorphous polyester, which leads to a wider color gamut. The content of the metal salt in the toner particles is preferably 0.2 parts by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the binder resin in the toner particles.
[0052] <External additives> The toner of the present invention may contain an external additive, if necessary, from the viewpoint of improving the flowability and adjusting the amount of triboelectric charge.
[0053] As the external additive, for example, inorganic fine particles such as silicon oxide (silica), titanium oxide (titania), aluminum oxide (alumina), strontium titanate, etc. are preferable. The inorganic fine particles are preferably hydrophobized with a hydrophobizing agent such as a silane compound, silicone oil, or a mixture thereof.
[0054] The specific surface area of the external additive is 10m 2 / g or more 50m 2 / g or less is preferable from the viewpoint of suppressing embedding of external additives.
[0055] The content of the external additive in the toner is preferably 0.1 parts by mass or more and 5.0 parts by mass or less with respect to 100 parts by mass of the toner particles.
[0056] For mixing the toner particles and the external additives, a mixer such as a Henschel mixer can be used.
[0057] <Career> From the viewpoint of obtaining stable images over a long period of time, the toner of the present invention is preferably mixed with a magnetic carrier and used as a toner for a two-component developer.
[0058] Examples of magnetic carriers include surface-oxidized iron powder, unoxidized iron powder, metal particles such as iron, lithium, calcium, magnesium, nickel, copper, zinc, cobalt, manganese, and rare earth elements, alloy particles of the above metals, oxide particles of the above metals, magnetic materials such as ferrite, and magnetic material-dispersed resin carriers (so-called resin carriers) that contain a magnetic material and a binder resin that holds the magnetic material in a dispersed state.
[0059] <Method of manufacturing a kneaded material for toner> As a method for producing the toner particles, it is preferable to adopt a melt-kneading method from the viewpoint of controlling the crystallinity of the copper phthalocyanine in the toner particles and improving the dispersibility.
[0060] The melt-kneading method is a method for producing toner particles, which includes a process of melting and kneading a mixture containing a binder resin, a colorant (copper phthalocyanine in the present invention), a copper phthalocyanine derivative, and wax, and, if necessary, a wax dispersant, to obtain a melt-kneaded product (hereinafter, also simply referred to as the "melt-kneading process").
[0061] The procedure for producing toner particles using the melt-kneading method will be described below. In the following description, the term "pigment" includes a copper phthalocyanine composition made of copper phthalocyanine and a copper phthalocyanine derivative.
[0062] In order to achieve the effects of the present invention, it is preferable to include a pigment dispersion step (copper phthalocyanine composition dispersion step). It is preferable to uniformly mix the pigment, metal salt, and amorphous polyester resin, and then perform kneading. Through this step, a copper phthalocyanine composition dispersion dispersed in the amorphous polyester is obtained, and the copper phthalocyanine derivative is likely to interact with the hydroxyl group site of the amorphous polyester resin and the metal salt.
[0063] The raw material mixing step will be described as the step of uniformly mixing the above. In the raw material mixing step, at least the pigment, metal salt, and amorphous polyester resin are weighed out in predetermined amounts as the raw materials for the pigment dispersion, and then mixed. Examples of mixing devices include a double con mixer, a V-type mixer, a drum mixer, a super mixer, a Henschel mixer, and a Nauta mixer.
[0064] The pigment dispersion raw materials thus blended and mixed are then fed into a melt kneader and melt kneaded at a temperature at which the melt viscosity of the amorphous polyester resin is 6000 Pa·sec or less, whereby the pigment and metal salt are uniformly dispersed to obtain a pigment dispersion. In the melt kneading step, for example, a batch kneader such as a kneader, a pressure kneader, or a Banbury mixer, or a continuous kneader can be used.
[0065] In the raw material mixing process for toner particles, the materials constituting the toner particles, such as the binder resin and colorant (copper phthalocyanine) or the above-mentioned pigment dispersion, and wax, and if necessary, the charge control agent, are weighed out in predetermined amounts, blended, and mixed. Examples of the mixing device include a double con mixer, a V-type mixer, a drum type mixer, a super mixer, a Henschel mixer, a Nauta mixer, and a Mechano Hybrid (manufactured by Nippon Coke & Engineering Co., Ltd.).
[0066] Next, the mixed materials are melted and kneaded to disperse the colorant (copper phthalocyanine) in the binder resin. In the melt-kneading process, a batch kneader such as a pressure kneader or a Banbury mixer, or a continuous kneader can be used. Due to the advantage of continuous production, single-screw or twin-screw extruders are mainstream. For example, KTK type twin-screw extruder (manufactured by Kobe Steel, Ltd.), TEM type twin-screw extruder (manufactured by Toshiba Machine Co., Ltd.), PCM kneader (manufactured by Ikegai Co., Ltd.), twin-screw extruder (manufactured by KCK Corporation), Co-Kneader (manufactured by Buss Co., Ltd.), and Kneadex (manufactured by Nippon Coke and Engineering Co., Ltd.) can be mentioned.
[0067] The kneaded product obtained by melt kneading may be rolled using a two-roll mill or cooled with water in a cooling step.
[0068] The cooled kneaded product is pulverized to a desired particle size in a pulverizing process. In the pulverizing process, the product is coarsely pulverized in a pulverizer, and then finely pulverized in a fine pulverizer. Examples of pulverizers that perform coarse pulverization include crushers, hammer mills, and feather mills. Examples of fine pulverizers that perform fine pulverization include the Cryptron System (manufactured by Kawasaki Heavy Industries, Ltd.), Super Rotor (manufactured by Nisshin Engineering, Inc.), Turbo Mill (manufactured by Turbo Kogyo Co., Ltd.), and fine pulverizers using an air jet system.
[0069] Thereafter, if necessary, the toner particles are classified using a classifier or a sieve. Examples of the classifier or sieve include an inertial classification type Elbow Jet (manufactured by Nittetsu Mining Co., Ltd.), a centrifugal classification type Turboplex (manufactured by Hosokawa Micron Corporation), a TSP Separator (manufactured by Hosokawa Micron Corporation), and a Faculty (manufactured by Hosokawa Micron Corporation).
[0070] Thereafter, if necessary, for example, to give the toner fluidity or to adjust the chargeability, external additives such as inorganic fine particles and resin particles are added and mixed (externally added) with the toner particles to obtain the toner. The mixing can be performed by a mixing device having a rotor having an agitating member and a main casing provided with a gap between the agitating member and the main casing.
[0071] Examples of mixing devices include a Henschel mixer (manufactured by Mitsui Mining Co., Ltd.), a Super Mixer (manufactured by Kawata Co., Ltd.), a Ribocone (manufactured by Okawara Manufacturing Co., Ltd.), a Nauta mixer, a Turbulizer, a Cyclomix, a Nobilta (manufactured by Hosokawa Micron Co., Ltd.), a Spiral Pin Mixer (manufactured by Pacific Machinery Co., Ltd.), and a Loedige Mixer (manufactured by Matsubo Co., Ltd.). In particular, a Henschel mixer (manufactured by Mitsui Mining Co., Ltd.) is suitable for uniformly mixing the external additive and the toner particles and for breaking up aggregates of the external additive.
[0072] Examples of mixing conditions include the processing amount, the rotation speed of the stirring shaft, the stirring time, the shape of the stirring blade, and the temperature inside the tank.
[0073] In cases where coarse aggregates of additives are present in a free state in the obtained toner, a sieving machine or the like may be used as necessary.
[0074] <Measurement, analysis> Next, the measurement and analysis techniques used in the present invention will be described.
[0075] <Method for measuring the hydroxyl value of resin> The hydroxyl value is the mass [mg] of potassium hydroxide required to neutralize the acetic acid bonded to the hydroxyl group when 1 g of a sample is acetylated. The hydroxyl value of the binder resin is measured in accordance with JIS K0070-1992. Specifically, it is measured according to the following procedure.
[0076] (1) Preparation of reagents Put 25 g of special grade acetic anhydride into a 100 mL measuring flask, add pyridine to make the total volume 100 mL, and shake thoroughly to obtain the acetylation reagent. Store the obtained acetylation reagent in a brown bottle to avoid contact with moisture, carbon dioxide, etc.
[0077] Dissolve 1.0 g of phenolphthalein in 90 mL of ethyl alcohol (95% by volume), and add ion-exchanged water to make 100 mL to obtain a phenolphthalein solution.
[0078] Dissolve 35g of special grade potassium hydroxide in 20mL of water and add ethyl alcohol (95% by volume) to make 1L. Leave in an alkali-resistant container for 3 days to avoid contact with carbon dioxide gas, etc., then filter to obtain potassium hydroxide solution. Store the resulting potassium hydroxide solution in an alkali-resistant container. The factor of the potassium hydroxide solution is calculated by placing 25mL of 0.5mol / L hydrochloric acid in an Erlenmeyer flask, adding several drops of the phenolphthalein solution, and titrating with the potassium hydroxide solution, from the amount of potassium hydroxide solution required for neutralization. The 0.5mol / L hydrochloric acid used is prepared in accordance with JIS K8001-1998.
[0079] (2) Operation (A) Main Test Weigh out 1.0 g of the crushed binder resin sample into a 200 mL round-bottom flask, and add 5.0 mL of the acetylation reagent using a volumetric pipette. If the sample is difficult to dissolve in the acetylation reagent, add a small amount of special grade toluene to dissolve it.
[0080] Place a small funnel on the mouth of the flask and immerse about 1 cm of the bottom of the flask in a glycerin bath at about 97°C and heat it. At this time, it is preferable to cover the base of the neck of the flask with a piece of cardboard with a round hole in it to prevent the temperature of the neck of the flask from rising due to the heat of the bath.
[0081] After 1 hour, remove the flask from the glycerin bath and allow it to cool. After allowing it to cool, add 1 mL of water through the funnel and shake to hydrolyze the acetic anhydride. To ensure complete hydrolysis, heat the flask again in the glycerin bath for 10 minutes. After allowing it to cool, wash the funnel and the walls of the flask with 5 mL of ethyl alcohol.
[0082] Add a few drops of the above phenolphthalein solution as an indicator and titrate with the above potassium hydroxide solution. The end point of the titration is when the light red color of the indicator continues for about 30 seconds.
[0083] (B) Blank test The titration is carried out in the same manner as above, except that no sample of the binder resin is used.
[0084] (3) The obtained result is substituted into the following formula to calculate the hydroxyl value. A = [{(BC) × 28.05 × f} / S] + D
[0085] Here, A: hydroxyl value (mgKOH / g), B: amount of potassium hydroxide solution added for the blank test (mL), C: amount of potassium hydroxide solution added for the main test (mL), f: factor of the potassium hydroxide solution, S: sample (g), D: acid value of the binder resin (mgKOH / g).
[0086] <Measurement of wax melting point (peak temperature of maximum endothermic peak)> The peak temperature of the maximum endothermic peak of the wax is measured using a differential scanning calorimeter (product name: Q1000, manufactured by TA Instruments) in accordance with ASTM D3418-82. The melting points of indium and zinc are used for temperature correction of the detector of the device, and the heat of fusion of indium is used for heat correction.
[0087] Specifically, about 5 mg of the sample is weighed out and placed in an aluminum pan. An empty aluminum pan is used as a reference, and the measurement is performed at a temperature rise rate of 10°C / min in the measurement temperature range of 30°C to 200°C. In the measurement, the temperature is raised once to 200°C, then lowered to 30°C, and then raised again. The temperature showing the maximum endothermic peak of the DSC curve in the range of 30°C to 200°C during this second temperature rise process is taken as the melting point of the wax (peak temperature of the maximum endothermic peak).
[0088] <Sulfo group of copper phthalocyanine derivative> The average amount of sulfo groups introduced is determined by the ratio of the amount of S and Cu present, S / Cu. The measurement of fluorescent X-rays conforms to JIS K 0119-1969, and is specifically as follows.
[0089] The measurement equipment used is a wavelength dispersive X-ray fluorescence analyzer "Axios" (PANalytical) and the accompanying dedicated software "SuperQ ver.4.0F" (PANalytical) for setting measurement conditions and analyzing measurement data. Rh is used as the anode of the X-ray tube, the measurement atmosphere is vacuum, the measurement diameter (collimator mask diameter) is 27 mm, and the measurement time is 10 seconds. As the detector, a known detector such as a proportional counter (PC) or a scintillation counter (SC) can be used. The pigment sample is measured to detect the amount of S and the amount of Cu, and the average amount introduced is determined by the ratio S / Cu.
[0090] <Alkyl groups of copper phthalocyanine derivatives, alkyl groups contained in sulfonic acid alkyl ester groups> The length of the alkyl moiety is measured using a rapifleX MALDI PharmaPulse (BRUKER), mass is analyzed by TOF-MS, and the amount of copper phthalocyanine and sulfo group is subtracted. The sample is placed in the chamber and measured. Ionization is performed using a N2 laser at an accelerating voltage of ±20 kV. Mass calibration is performed by quantifying the sulfo group with fluorescent X-rays, measuring the total molecular weight with TOF-MS, and then subtracting the molecular weight of the sulfo group and copper phthalocyanine to calculate the average amount of alkyl groups introduced. EXAMPLES
[0091] <Production Example of Copper Phthalocyanine Pigment 1> Pigment (CI Pigment Blue 15:3) 100 parts by weight Copper phthalocyanine derivative 1 5 parts by weight (Average amount of sulfo groups introduced is 2.0, average amount of alkyl groups introduced is 2.0, alkyl carbon number is 15) Tetrahydrofuran 100 parts by weight The above formulation was mixed with 30 parts by mass of zirconia beads having a diameter of 1 mm for 5 hours in a paint shaker, and then the zirconia beads were removed by filtration through a metal mesh.
[0092] The obtained dispersion liquid of the copper phthalocyanine pigment was subjected to distillation to remove tetrahydrofuran using a rotary evaporator, and further dried in a reduced pressure drying oven at 50° C. to obtain a copper phthalocyanine composition, Copper Phthalocyanine Pigment 1. The composition is shown in Table 1.
[0093] <Production Examples of Copper Phthalocyanine Pigments 2-14> Copper phthalocyanine pigments 2 to 14 were produced in the same manner as in the production of copper phthalocyanine pigment 1, except that the constitution of the copper phthalocyanine derivative was changed as shown in Table 1.
[0094] [Table 1]
[0095] <Production example of amorphous polyester 1> Polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane 75 parts by weight Terephthalic acid 25 parts by weight ·Adipic acid 8 parts by mass Titanium tetrabutoxide 0.5 parts by mass The above formulation was placed in a 4 L, four-necked glass flask, which was equipped with a thermometer, a stirrer, a condenser and a nitrogen inlet tube, and placed in a mantle heater.
[0096] Next, the atmosphere in the flask was replaced with nitrogen gas, and the temperature was gradually raised with stirring, and the mixture was reacted for 4 hours at a temperature of 200° C. with stirring (first reaction step).
[0097] Thereafter, 1.2 parts by mass (0.006 mol) of trimellitic anhydride was added and reacted at 180° C. for 1 hour (second reaction step), to obtain amorphous polyester 1. The hydroxyl value of amorphous polyester 1 was 55 mgKOH / g.
[0098] <Production Examples of Amorphous Polyesters 2 to 7> Amorphous polyesters 2 to 7 were obtained in the same manner as for amorphous polyester 1, except that polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane, terephthalic acid, synthesis conditions, etc. were changed as shown in Table 2.
[0099] [Table 2]
[0100] <Production of Pigment Dispersion 1> Pigment 1 20 parts by weight Metal salt (light calcium carbonate, number average particle size 0.4 μm) 20 parts by weight Amorphous polyester 1 60 parts by weight The above materials were mixed in a Henschel mixer (FM-75, manufactured by Mitsui Mining Co., Ltd.) at a rotation speed of 20 s. -1After mixing for 5 minutes, the mixture was kneaded at 120° C. in a twin-screw kneader (PCM-30, manufactured by Ikegai Corporation). The kneaded mixture was cooled and coarsely pulverized in a pin mill to a volume average particle size of 100 μm or less to obtain a coarsely pulverized product of pigment dispersion 1. The composition is shown in Table 3.
[0101] <Production of Pigment Dispersions 2 to 5> Except for changing the pigment and the amorphous polyester, Pigment Dispersions 2 to 5 were produced in the same manner as Pigment Dispersion 1. The compositions are shown in Table 3.
[0102] [Table 3]
[0103] <Toner 1 Manufacturing Example> Amorphous polyester 1 85 parts by weight Fischer-Tropsch wax (hydrocarbon wax; melting point 90°C) 5 parts by mass Pigment dispersion 1 25 parts by weight The above materials were mixed in a Henschel mixer (FM-75, manufactured by Mitsui Mining Co., Ltd.) at a rotation speed of 20 s. -1 After mixing for 5 minutes at 100° C., the mixture was kneaded in a twin-screw kneader (PCM-30, manufactured by Ikegai Corporation). The barrel temperature during kneading was set so that the outlet temperature of the kneaded product was 115° C. The outlet temperature of the kneaded product was directly measured using a handheld thermometer HA-200E manufactured by Anritsu Keiki Co., Ltd.
[0104] The kneaded product obtained was cooled and coarsely pulverized to 1 mm or less using a hammer mill to obtain a coarsely pulverized product. The coarsely pulverized product obtained was finely pulverized using a mechanical pulverizer (T-250, manufactured by Turbo Kogyo Co., Ltd.). It was further classified using Faculty F-300 (manufactured by Hosokawa Micron Corporation) to obtain toner particles 1. The operating conditions were a classifying rotor rotation speed of 130 s -1 , Dispersion rotor speed 120s -1 It was decided.
[0105] To 100 parts by mass of the obtained toner particles, hydrophobic silica (BET: 200m 2 / g) 1.0 mass part, titanium oxide fine particles surface-treated with isobutyltrimethoxysilane (BET: 80m 2 1.0 part by mass of 1.0 1 / g of 10 ... -1 The mixture was mixed at a rotation time of 10 min to obtain Toner 1. The composition is shown in Table 4.
[0106] <Production Examples of Toners 2 to 29> Toners 2 to 29 were produced in the same manner as Toner 1, except that the type of amorphous polyester, pigment or pigment dispersion, etc. were changed as shown in Table 4. Note that the columns "Amorphous polyester" and "Metal salt" in Table 4 do not include the amorphous polyester or metal salt blended in the pigment dispersion.
[0107] [Table 4]
[0108] <Production Example of Magnetic Core Particle 1> Process 1 (weighing and mixing process): ·Fe2O362.7 parts by mass ·MnCO329.5 parts by mass ·Mg(OH)26.8 parts by mass ·SrCO31.0 parts by mass The ferrite raw materials were weighed so as to obtain the above composition ratio, and then crushed and mixed for 5 hours in a dry vibration mill using stainless steel beads with a diameter of 1 / 8 inch. Step 2 (pre-firing step): The obtained pulverized material was made into pellets of about 1 mm square using a roller compactor. The pellets were passed through a vibrating sieve with 3 mm openings to remove coarse powder, and then through a vibrating sieve with 0.5 mm openings to remove fine powder. The pellets were then fired in a burner-type firing furnace at 1000°C for 4 hours in a nitrogen atmosphere (oxygen concentration 0.01% by volume) to produce calcined ferrite. The composition of the calcined ferrite obtained was as follows: (MnO)a(MgO)b(SrO)c(Fe2O3)d In the above formula, a = 0.257, b = 0.117, c = 0.007, and d = 0.393. Step 3 (Crushing step): After crushing to about 0.3 mm using a crusher, 30 parts by mass of water was added to 100 parts by mass of the calcined ferrite using zirconia beads with a diameter of 1 / 8 inch, and the mixture was crushed in a wet ball mill for 1 hour. The slurry was crushed for 4 hours in a wet ball mill using alumina beads with a diameter of 1 / 16 inch to obtain a ferrite slurry (finely crushed calcined ferrite). Process 4 (granulation process): To the ferrite slurry, 1.0 parts by mass of ammonium polycarboxylate as a dispersant and 2.0 parts by mass of polyvinyl alcohol as a binder were added per 100 parts by mass of the calcined ferrite, and the mixture was granulated into spherical particles using a spray dryer (manufacturer: Okawara Kakoki). After adjusting the particle size of the resulting particles, the mixture was heated at 650°C for 2 hours using a rotary kiln to remove the organic components of the dispersant and binder. Step 5 (firing): In order to control the firing atmosphere, the material was heated from room temperature to 1300°C in a nitrogen atmosphere (oxygen concentration 1.00% by volume) in an electric furnace over a period of 2 hours, and then fired at 1150°C for 4 hours. The material was then cooled to 60°C over a period of 4 hours, returned from the nitrogen atmosphere to the air, and removed at a temperature of 40°C or less. Step 6 (sorting step): After crushing the agglomerated particles, low magnetic particles were removed by magnetic separation, and coarse particles were removed by sieving through a sieve with 250 μm openings to obtain magnetic core particles 1 having a volume distribution standard 50% particle size (D50) of 37.0 μm.
[0109] <Preparation of Coating Resin 1> Cyclohexyl methacrylate monomer 26.8% by mass Methyl methacrylate monomer 0.2% by mass Methyl methacrylate macromonomer 8.4% by mass (A macromonomer with a weight-average molecular weight of 5000 and a methacryloyl group at one end) Toluene 31.3% by mass Methyl ethyl ketone 31.3% by mass Azobisisobutyronitrile 2.0% by mass Among the above materials, cyclohexyl methacrylate, methyl methacrylate, methyl methacrylate macromonomer, toluene, and methyl ethyl ketone were placed in a four-necked separable flask equipped with a reflux condenser, a thermometer, a nitrogen inlet tube, and a stirrer, and nitrogen gas was introduced to replace the inside of the system with nitrogen gas. After that, the mixture was heated to 80°C, azobisisobutyronitrile was added, and the mixture was refluxed for 5 hours to polymerize. Hexane was poured into the resulting reaction product to precipitate a copolymer, and the precipitate was filtered and then vacuum dried to obtain coating resin 1. The obtained coating resin 1 was dissolved in 30 parts by mass, 40 parts by mass of toluene, and 30 parts by mass of methyl ethyl ketone to obtain polymer solution 1 (solid content 30% by mass).
[0110] <Preparation of coating resin solution 1> ·Polymer solution 1 (resin solid content concentration 30%) 33.3% by mass Toluene 66.4% by mass Carbon black (Regal 330; Cabot Corporation) 0.3% by mass (Primary particle size 25 nm, nitrogen adsorption specific surface area 94 m 2 / g, DBP oil absorption 75ml / 100g) The mixture was dispersed for 1 hour using a paint shaker with zirconia beads having a diameter of 0.5 mm. The resulting dispersion was filtered through a 5.0 μm membrane filter to obtain a coating resin solution 1.
[0111] <Magnetic Carrier 1 Manufacturing Example> (Resin coating process): Coating resin solution 1 was added to a vacuum degassing kneader maintained at room temperature so that the resin component was 2.5 parts by mass per 100 parts by mass of magnetic core particles 1. After addition, the mixture was stirred at a rotation speed of 30 rpm for 15 minutes, and after a certain amount of the solvent (80% by mass) had evaporated, the mixture was heated to 80°C while mixing under reduced pressure, and toluene was distilled off over 2 hours, after which it was cooled. The magnetic carrier obtained was separated into low magnetic products by magnetic separation, passed through a sieve with an opening of 70 μm, and then classified with a wind classifier to obtain magnetic carrier 1 having a 50% particle size (D50) of 38.2 μm based on volume distribution.
[0112] <Production example of two-component developer 1> Toner 1 was added in an amount of 8.0 parts by mass to magnetic carrier 1 in an amount of 92.0 parts by mass, and the mixture was mixed in a V-type mixer (V-20, manufactured by Seishin Enterprise Co., Ltd.) to obtain two-component developer 1.
[0113] <Production Examples of Two-Component Developers 2 to 29> In the production example of two-component developer 1, the same operation was carried out except that the combination of toners was changed as shown in Table 5, to obtain two-component developers 2 to 29.
[0114] Example 1 The above two-component developer 1 was used for evaluation.
[0115] A modified Canon full-color copier imageRUNNER ADVANCE C5255 was used as the image forming apparatus, two-component developer 1 was charged into the developer unit of the cyan station, and the DC voltage VDC of the developer carrier, the charging voltage VD of the electrostatic latent image carrier, and the laser power were adjusted so that the amount of toner carried on the electrostatic latent image carrier or paper was as desired, and the evaluation described below was performed. The modification was made so that the fixing temperature and process speed could be freely set.
[0116] The evaluation was performed based on the following evaluation methods, and the results are shown in Table 5.
[0117] [Method of evaluating toner saturation] The evaluation environment was normal temperature and humidity (23°C, 50% RH), and the evaluation paper was plain copy paper CS-680 (A4 paper, basis weight: 68 g / m 2 (sold by Canon Marketing Japan Inc.) was used.
[0118] First, in the evaluation environment, the amount of toner applied on the paper was changed to examine the relationship between image density and the amount of toner applied on the paper.
[0119] Next, the image density of the FFH image (solid area) was adjusted to 1.40, and the solid image was output. 50 The L1*, a1*, and b1* of a solid image were measured using a viewing angle of 2°.
[0120] In addition, C1* for each gradation was calculated using the following formula. C1*={(a1*) 2 +(b1*) 2} 0.5 The higher the C1*, the higher the saturation, and the evaluation was based on the following criteria. The evaluation results are shown in Table 7.
[0121] (Evaluation Criteria) A: 66 or above (Excellent) B: 63 or more, less than 66 (good) C: 60 or more and less than 63 (this level is not problematic in the present invention) D: Less than 60 (not acceptable in this invention)
[0122] [Method for evaluating toner color variation] The settings were left as they were when evaluating saturation, and the evaluation environment was changed to a high temperature and humidity environment (30°C, 80% RH), and L2*, a2*, and b2* of the solid image were measured. ΔE was calculated from the L*, a*, and b* values of the image. The evaluation results are shown in Table 5. ΔE={(L1 * -L2 * ) 2 +(a1 * -a2 * )2 +(b1 * -b2 * ) 2} 0.5 A: ΔE less than 2.0 (no visible color change) B: ΔE 2.0 or more and less than 3.0 (greater than A, but no color change can be confirmed by the naked eye) C: ΔE 3.0 or more and less than 4.0 (larger than B, but only slight color variation can be confirmed visually) D: ΔE 4.0 or more (larger than C, color variation can be visually confirmed)
[0123] [Method for evaluating toner density fluctuation] Next, a fixed amount of toner was replenished so that the toner concentration was constant for an image with a printing ratio of 1%, and 5,000 sheets (5k) of images were output.
[0124] After the 10K durability test, the amount of toner on the paper was changed to examine the relationship between image density and the amount of toner on the paper.
[0125] Next, the image density of the FFH image (solid area) was adjusted to 1.40, and the solid image was output. 50 The L3*, a3*, and b3* of the solid image were measured using a viewing angle of 2°.
[0126] ΔE was calculated from the L*, a*, and b* values of the initial image and the image after 5k durability. The evaluation results are shown in Table 5. ΔE={(L1 * -L3 * ) 2 +(a1 * -a3 * ) 2 +(b1 * -b3 * ) 2} 0.5 A: ΔE less than 2.0 (no visible color change) B: ΔE 2.0 or more and less than 3.0 (greater than A, but no color change can be confirmed by the naked eye) C: ΔE 3.0 or more and less than 4.0 (larger than B, but only slight color variation can be confirmed visually) D: ΔE 4.0 or more (larger than C, color variation can be visually confirmed)
[0127] [Examples 2 to 22] The evaluation was carried out in the same manner as in Example 1, except that the toner was changed as shown in Table 5. The results are shown in Table 5.
[0128] [Comparative Examples 1 to 7] The evaluation was carried out in the same manner as in Example 1, except that the toner was changed as shown in Table 5. The results are shown in Table 5.
[0129] [Table 5]
[0130] In Comparative Example 1, the hydroxyl value of the amorphous polyester is below the lower limit. It is believed that the sulfo group of the derivative is less likely to interact with the resin, resulting in poor saturation evaluation results.
[0131] In Comparative Example 2, the hydroxyl value of the amorphous polyester exceeds the upper limit. As a result, the color variation and the durability variation are deteriorated, which is considered to be due to the deterioration of the moisture property of the resin.
[0132] In Comparative Example 3, the number of carbon atoms in the alkyl portion of the derivative is below the lower limit. It is presumed that the interaction with the wax is reduced, resulting in poor charge retention and poor color and density stability.
[0133] In Comparative Example 4, the number of carbon atoms in the alkyl portion of the derivative exceeds the upper limit. It is presumed that if the number of carbon atoms is too large, the distance from the wax becomes too far. As a result, it is presumed that the interaction is reduced, the charge retention is deteriorated, and the color and density stability are deteriorated.
[0134] Comparative Example 5 does not contain an alkyl group of the derivative. It is considered that the interaction with the wax is lost, leading to deterioration in the charge retention and deterioration in the stability of the color gamut and density.
[0135] Comparative Example 6 does not contain a sulfo group, and contains an average introduction amount of 2.0 amine groups. It is believed that since amine groups do not easily interact with hydroxyl groups, no change occurs in the electronic state, resulting in a low chroma value.
[0136] Comparative Example 7 is a case where no sulfo group is contained. When no sulfo group is contained, there is no interaction with the hydroxyl group site of the amorphous polyester, and no change occurs in the electronic state. This is thought to result in a deterioration in saturation.
Claims
1. A toner having toner particles containing an amorphous polyester, a hydrocarbon wax, and a copper phthalocyanine composition, The hydroxyl value of the amorphous polyester is 40 mgKOH / g or more and 90 mgKOH / g or less, The copper phthalocyanine composition contains C. I. Pigment Blue 15:3 and a copper phthalocyanine derivative, and the copper phthalocyanine derivative is a compound represented by the following general formula (1): 【Chemistry 1】 [In the formula, R 1 ~R 8 represents a hydrogen atom, a sulfo group, an alkyl group, or a sulfonic acid alkyl ester group, R 1 ~R 8 At least one of the groups is a sulfo group; R 1 ~R 8 at least one of is an alkyl group or a sulfonic acid alkyl ester group, and the alkyl group and the alkyl group contained in the sulfonic acid alkyl ester group are alkyl groups having 5 to 40 carbon atoms.
2. 2. The toner according to claim 1, wherein the melting point of the hydrocarbon wax is 70° C. or more and 130° C. or less.
3. 3. The toner according to claim 1, which contains a metal salt.
4. The toner according to any one of claims 1 to 3, wherein a mixing ratio of the C. I. Pigment Blue 15:3 and the copper phthalocyanine derivative is 20:1 to 100:1 in terms of mass ratio.
Citation Information
Patent Citations
Microcapsule toner
JP1985026951A
Water-base ink
JP1990024367A
Coloring composition, method for production thereof, and coloring method
JP2009132911A
Nano-sized particle of phthalocyanine pigment
JP2009215554A
Electrophotographic cyan toner
JP2012053321A